Chromosomes and sex ratio of the collared lemming, Dicrostonyx richardsoni - Malcolm, Jay R.; Brooks, Ronald J.; Bogart, James P. (Canadian Journal of Zoology, 1986)
The chromosomes of 18 laboratory-born Dicrostonyx richardsoni (= D. groenlandicus richardsoni) were examined. Eight females had 2n = 44 and two large metacentric chromosomes, three females and two males had 2n = 43 and three large metacentrics, and two females and three males had 2n = 42 and four large metacentrics. The observed chromosomal polymorphism was explained as a Robertsonian transformation in which metacentrics underwent centric fission to form two telocentrics, or two telocentrics fused to form a metacentric. No chromosomal differences were observed between males and females that had the same number of large metacentrics. The laboratory sex ratio at weaning was 0.38:1 (363 males, 596 females). Observed and expected distributions of proportions of male offspring among dams were significantly different if dams were assumed to produce males with binomial probability 0.5, or with probability 0.38. There was qualitative support for three female types, each producing males with probability 0.50, 0.25, or 0.33, as has been hypothesized for Dicrostonyx torquatus from Asia.